Conversion of natural feedstocks to porous carbons via carbonization in fluidized catalyst bed followed by leaching the feedstock mineral template phase: A comparison of biomass and sedimentary raw materials - Eletsky P. M. Petr Mikhaylovich; Dubinin Yu. V. Yury Vladimirovich; Yazykov N. A. Nikolay Alekseevich; Tabakaev R. B. Roman Borisovich; Okotrub K. A. Konstantin Alexandrovich; Yakovlev V. A. Vadim Anatoljevich (2022, 2022)
Title screen